Clinical and ultrasonographic features preceding a difficult-to-treat phenotype in psoriatic arthritis: a retrospective real-world exploratory cohort study - Elisa Bellis; Mariele Gatto; Claudio Cruciani; Federico Favaro; Eleonora Croce; Francesca Luppi; Federica Agugliaro; Claudia Garulli; Federica Laterza; Gloria Crepaldi; Valeria Data; Claudia Lomater; et al. (Frontiers in Immunology, 2026)
Objectives To explore clinical and ultrasonographic features preceding the development of a difficult-to-treat (D2T) phenotype in a real-world cohort of patients with psoriatic arthritis (PsA). Materials and methods In this retrospective cohort study, consecutive PsA patients (January 2020-September 2024) were included. D2T PsA was defined according to a pragmatic operational definition based on persistent disease activity despite ≥2 biologic or targeted synthetic disease-modifying antirheumatic drugs (b/tsDMARDs). Baseline demographic and clinical data were collected. Ultrasound (US) assessment included synovitis, erosions, tenosynovitis, enthesitis, bursitis, and dactylitis, using approved definitions and scoring systems. Predictors of D2T were analyzed using Cox regression models. Results A total of 152 patients were included (81 D2T, 71 non-D2T), with US data available in 117. D2T patients were younger at diagnosis (47.3 ± 11.4 vs 53.2 ± 10.1 years, p<0.001). In the overall multivariable Cox model, no baseline clinical variable independently predicted D2T. However, when diagnostic delay was categorized using a ≥1-year threshold, Kaplan-Meier analysis showed reduced D2T-free survival in patients with diagnostic delay ≥1 year (log-rank p=0.025). When analyses were stratified according to predominant disease pattern, diagnostic delay ≥1 year remained independently associated with D2T in both peripheral [HR 1.74 (95% CI 1.05–2.88), p=0.032] and axial PsA [HR 3.18 (1.22–8.27), p=0.018]. In axial disease, fibromyalgia [HR 2.45 (1.12–5.36), p=0.025] and enthesitis [HR 2.49 (1.08–5.70), p=0.033] were additional predictors. In multivariable Cox regression, higher mean bilateral Global OMERACT/EULAR US Synovitis Score (GLOESS) at the first metatarsophalangeal joint (MTP) was directly associated [HR 3.21 (1.47–6.99), p=0.003] while mean GLOESS at the wrist was inversely [HR 0.52 (0.33–0.80), p=0.003] associated with D2T. Conclusions In this retrospective exploratory cohort, diagnostic delay of at least one year and selected US features were associated with later D2T PsA classification. First MTP GLOESS was positively associated with D2T classification, whereas wrist GLOESS showed an inverse association. These findings should be interpreted cautiously because of the retrospective design, variable US timing, and need for external validation.